Education of teachers of indigenous students in early childhood services and schools discussion paper - Ministerial Council on Education, Employment, Training and Youth Affairs (Australia). Taskforce on Indigenous Education (Carlton South, Vic. : Ministerial Council on Education, Employment, Training and Youth Affairs, 2001)
The discussion paper includes topics on the international and Australian trends in this context, indigenous education issues and professional standards for teachers.
"MCEETYA Taskforce on Indigenous Education discusssion paper June 2001".
System requirements: Adobe Acrobat reader to access documents in PDF format.
Title from title screen (viewed on Apr. 12, 2002).
Text.
Mode of access: Internet via World Wide Web. Available at: http://www.curriculum.edu.au/mctyapdf/educationofteachersinecs.pdf
Selected for archiving
Keywords: Early childhood teachers -- Training of -- Australia; Indigenous peoples -- Education (Early childhood) -- Australia; Education - Early childhood; Education - Teachers - Teacher education